EVOLVING DEFINITION OF SOCIOMUSEOLOGY: PROPOSAL FOR REFLECTION (Cadernos de Sociomuseologia, 2009)
Sociomuseology expresses a considerable amount of the effort made to suit museological facilities to the conditions of contemporary society. The process of opening up the museum, as well as its organic relation with the social context that infuses it with life, has resulted in the need to structure and clarify the relations, notions and concepts that may define this process. Sociomuseology is thus a scientific field of teaching, research and performance which emphasizes the articulation of museology, in particular, with the areas of knowledge covered by Human Sciences, Development Studies, Services Science, and Urban and Rural Planning. The multidisciplinary approach of Sociomuseology aims to strengthen the acknowledgement of museology as a resource for the sustainable development of Humanity, based on equal opportunities as well as social and economic inclusion. Sociomuseology bases its social intervention on mankind’s cultural and natural heritage, both tangible and intangible. What characterizes Sociomuseology is not so much the nature of its premises and its goals, as is the case with other areas of knowledge, but the interdisciplinary focus which makes it draw on perfectly consolidated areas of knowledge and relate them with Museology itself.